Gendering Labour History Across Borders - Sangster, Joan (Labour History Review, 2010)
Explores the evolution of a new women's labour history in the post-1960s era, with attention to the similarities and differences characterizing scholarship in Britain, Canada and the United States. The debates the field animated, and how these shifted over time as the political and intellectual context changed, are critically and comparatively examined. By tracing the movement of ideas, themes and inspiration across borders, one can gain a better understanding of the transnational creation of a feminist labour history.